2021
DOI: 10.1097/md.0000000000026795
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar laminotomy and replantation for the treatment of lumbar spinal epidural lipomatosis

Abstract: Rationale:Lumbar spinal epidural lipomatosis (SEL) is a rare condition characterized by excessive overgrowth of extradural fat within the lumbar spinal canal. Surgical decompression is commonly performed to treat symptomatic SELs. Fenestration or laminectomy with epidural fat debulking was a routine surgical procedure according to the literature, that may be causing postoperative lumbar instability. In the present study, we presented a brief report of lumbar SEL and introduced another surgical approach.Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…[ 19 ] With the intensification of population aging and the continuous change of lifestyle, its incidence has been increasing year by year, which seriously threatens people’s quality of life. [ 2 , 20 ] Currently, surgery is the main treatment for patients with lumbar spinal stenosis. [ 21 ] Moreover, we found that LncRNA GAS5 gene expression were up-regulated in patients undergoing lumbar spinal canal decompression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 19 ] With the intensification of population aging and the continuous change of lifestyle, its incidence has been increasing year by year, which seriously threatens people’s quality of life. [ 2 , 20 ] Currently, surgery is the main treatment for patients with lumbar spinal stenosis. [ 21 ] Moreover, we found that LncRNA GAS5 gene expression were up-regulated in patients undergoing lumbar spinal canal decompression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Compression of the spinal cord can cause such irreversible pathological changes as numbness of the lower limbs, weakness in walking, paralysis and incontinence of urine and feces, which seriously impacts the patients’ quality of life. [ 2 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the thoracic and lumbar spine, laminoplasty, laminectomy, and fusion procedures have been described. 3 , 30–32 Less invasive tissue-preserving decompression using endoscopic techniques has also been described. 10 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Surgery interventions should be considered when conservative treatments fail and clinical symptoms deteriorate rapidly ( 14 ). As for the surgical methods, extensive laminectomy and excision of the adipose tissue are the most commonly used options ( 15 ). So far, there has been no report to treat lumbar lipomatosis using the percutaneous uniportal full-endoscopic technique.…”
Section: Introductionmentioning
confidence: 99%